Systemic-onset juvenile idiopathic arthritis: a challenge for the dermatologist. - Barreto-Castilla, V.; Torres-Langhammer, P.; Rodriguez-Lechtig, B.; Giraldo, M.J.; Velandia Siabato, A.; Motta , A. (European Journal of Pediatric Dermatology, 2025)
Systemic-onset juvenile idiopathic arthritis (sJIA) is a rare but potentially life-threatening inflammatory condition affecting children. Its evanescent skin eruption may represent a crucial diagnostic clue. We report the case of a 2-year-old boy presenting with daily high spiking fevers, arthralgia, and a transient salmon-colored maculopapular rash coinciding with febrile episodes. Physical examination and laboratory findings – including leukocytosis, elevated inflammatory markers, and hyperferritinemia – supported the diagnosis of systemic-onset juvenile idiopathic arthritis associated with partial macrophage activation syndrome (MAS). Ultrasound confirmed arthritis in multiple joints. Initial treatment with systemic corticosteroids and methotrexate was later escalated with the addition of cyclosporine and tocilizumab, resulting in clinical improvement. This case highlights the importance of recognizing the subtle and fleeting cutaneous signs of this disease, which may precede or accompany systemic symptoms. Dermatologists play a key role in the early recognition and referral of such cases to pediatric rheumatologists.